Implementation of ESG principles at water supply enterprises in the context of digitalization - V. P. Poluyanov (Путеводитель предпринимателя)
The basic principles of ESG (Environmental, Social, and Corporate Governance) have achieved wide popularity throughout the world and, to a certain extent, have found their way into the conditions of the strategy for sustainable development of the our. However, a study of publications showed a lack of generally accepted understanding of what exactly these principles should reflect in relation to a particular industry.The paper examines the problem of industry differentiation of ESG principles in relation to housing and communal services, exacerbated by the diversity of the industry. It is noted that water supply is considered as an equal direction of sustainable economic development among 9 main ones. The key areas of the concept of sustainable development are compliance with environmental, social and economic principles in the operation of the enterprise. The same principles form the basis of the ESG approach.The purpose of the work is to substantiate the main directions for implementing ESG principles in the strategy for sustainable development of water supply.The work proposes the content of key components for the implementation of ESG principles in Russian water supply. It is also proposed to use these principles as components in the preparation of a system of indicators of consumer quality of corporate information systems of enterprises that provide relevant services.One of the practical directions for introducing ESG principles into the activities of water supply enterprises is their consideration in the process of developing the enterprise’s corporate information system. The work identifies specific principles that are included in the requirements for consumer qualities of a software product at the design stage of development and improvement of an enterprise’s corporate information system.